Apolipoprotein A5 in health and disease - Hubáček, J A; Adámková, V; Vrablík, M; Kadlecová, M; Zicha, J; Kunes, J; Pitha, J; Suchánek, P; Poledne, R (Physiological research, 2009)
High plasma levels of triglycerides (TG) are an independent risk factor in the development of cardiovascular disease, with about 50 % of the final levels being determined genetically. Apolipoprotein A5 (APOA5) is the last discovered member of the apolipoprotein APOA1/C3/A4 gene cluster, found by comparative sequencing analysis. The importance of APOA5 gene for determination of plasma triglyceride levels has been suggested after development of transgenic and knock-out mice (transgenic mice displayed significantly reduced TG, whereas knock-out mice had high TG). In Czech population, alleles C-1131 and Trp19 are associated with elevated levels of plasma TG and higher risk of myocardial infarction development. These alleles also play some role in nutrigenetics and actigenetics of lifestyle interventions leading to the plasma cholesterol changes as well as in the pharmacogenetics of statin treatment. On the contrary, APOA5 mutations detected in Czech population did not show strict effect on plasma TG levels. Val153 --> Met variant exhibit the sex-specific effect of HDL-cholesterol levels. The suggested roles of APOA5 variants in determination of the plasma remnant particles, plasma concentrations of C-reactive protein or some anthropometrical parameters were excluded.
Keywords: Genetic Predisposition to Disease; Rats; Triglycerides; hypercholesterolemie; apolipoproteiny; Disease Models, Animal; Risk Assessment; mužské pohlaví; infarkt myokardu; Mice; fenotyp; apolipoproteiny A; polymorfismus genetický; myši knockoutované; krysa rodu Rattus; Apolipoproteins; Myocardial Infarction; Polymorphism, Genetic; Apolipoprotein A-V; Phenotype; modely nemocí na zvířatech; ženské pohlaví; hodnocení rizik; zvířata; Humans; Apolipoproteins A; triglyceridy; Mice, Knockout; frekvence genu; myši; Gene Frequency; apolipoprotein A-V; genetická predispozice k nemoci; Female; Hypercholesterolemia; lidé; Male; Animals